Analsis Strategi Peningkatan Penerimaan Pajak Restoran Kota Bekasi Tahun 2020 Di Masa Pandemi Covid-19 (Studi Kasus Pada Badan Pendapatan Daerah Kota Bekasi Di Masa Pandemi Covid-19) - Adin Dahuri; Dwikora Harjo; Christy Balancia (Jurnal Pajak Vokasi (JUPASI), 2021)
This study is conducted to analyze the strategy for increasing Bekasi City Restaurant Tax Revenue in 2020 during the Covid-19 pancemic at Revenue Agency of Bekasi City. The result of this study indicates that the strategy formulation and implementation in the Restaurant Tax revenue in its application did not rum well, especially during the Covid-19 pandemic. Indeed in 2018 t0 2019 there was an increment by 3.94% but in the following period tthere was a decrement by  7.7%. Kotten theory applied in the study that consisting of four classification strategies : organizational strategy, program strategy resources support strategy and institutional strategy. A qualitative approach with a descriptive method used in this study. Observation, documentation and interview were used as data collection. The result of this study indicates that the strategy for increasing Bekasi City Restaurant Tax revenue in 2020 did not run well. It was shown in the failure in target achievement that contributed by large number of taxpayers who did not realize of SIPDAH program due to unsufficient of socialization effors